(untitled) (Journal of Contemporary Issues in Accounting, 2023)
This study examines the effect of the fraud diamond model and fraudulent financial reporting of deposit money banks in Nigeria. The study specifically evaluates the effect of pressure, opportunity, rationalization, and capability on fraudulent financial reporting of DMBs. The study adopts the ex post facto research design. The population comprised all listed deposit money banks on the Nigerian Exchange Group (NGX) as of the end of 2022. The final sample was 13 DMBs based on data availability. The study utilises secondary data from the annual financial statements of the DMBs for the years 2012-2022. The data were analyzed using descriptive and inferential statistical analyses. The hypotheses were tested using the multiple linear regression technique. The results showed that CFT has a non-significant negative effect on the fraudulent financial reporting of listed Deposit Money Banks; RPT has a non-significant effect on the fraudulent financial reporting of listed Deposit Money Banks; ECD has a significant negative effect on the fraudulent financial reporting of listed Deposit Money Banks; and, PEF has a significant positive effect on the fraudulent financial reporting of listed Deposit Money Banks. Based on this, the study recommends that managers should carefully watch cashflow trend to avoid lowering the financial rating of DMBs as excessive operating cashflow indicates suboptimal managerial decisions; and, shareholders monitor firms for related party transactions which is suggestive of weak corporate governance which lowers the fraudulent financial reporting of Deposit Money Banks; among others.